2019
DOI: 10.1073/pnas.1911304116
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale coupling of junctophilin-2 and ryanodine receptors regulates vascular smooth muscle cell contractility

Abstract: Junctophilin proteins maintain close contacts between the endoplasmic/sarcoplasmic reticulum (ER/SR) and the plasma membrane in many types of cells, as typified by junctophilin-2 (JPH2), which is necessary for the formation of the cardiac dyad. Here, we report that JPH2 is the most abundant junctophilin isotype in native smooth muscle cells (SMCs) isolated from cerebral arteries and that acute knockdown diminishes the area of sites of interaction between the SR and plasma membrane. Superresolution microscopy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 40 publications
3
52
0
Order By: Relevance
“…To investigate this hypothesis, we utilized immunofluorescence labeling in conjunction with ground state depletion followed by individual molecule return (GSDIM) superresolution microscopy (34)(35)(36) in native BSMCs to examine the subcellular nanoscale colocalization of TRPML1 channel clusters with RyR2s and the LEL membrane-bound protein, Lamp-1 (lysosomal-associated membrane protein 1). Using DNA origamibased nanorulers, we have previously shown that the lateral resolution of our GSDIM system is 20 to 40 nm (37)(38)(39).…”
Section: Nanoscale Localization Of Trpml1-positive Lels To Ryr2 Clustmentioning
confidence: 96%
“…To investigate this hypothesis, we utilized immunofluorescence labeling in conjunction with ground state depletion followed by individual molecule return (GSDIM) superresolution microscopy (34)(35)(36) in native BSMCs to examine the subcellular nanoscale colocalization of TRPML1 channel clusters with RyR2s and the LEL membrane-bound protein, Lamp-1 (lysosomal-associated membrane protein 1). Using DNA origamibased nanorulers, we have previously shown that the lateral resolution of our GSDIM system is 20 to 40 nm (37)(38)(39).…”
Section: Nanoscale Localization Of Trpml1-positive Lels To Ryr2 Clustmentioning
confidence: 96%
“…In further studies, single SMCs from cerebral arteries isolated from control and Stim1-smKO mice were enzymatically dispersed, immunolabeled with an anti-STIM1 primary antibody, and imaged using a GSDIM (ground state depletion followed by individual molecule return) superresolution microscopy system, which we previously showed using DNA-origami-based nanorulers has a lateral resolution of 20-40 nm (49)(50)(51). VSMCs from control mice exhibited punctate STIM1 protein clusters (Figure 1B).…”
Section: Stim1-smko Mice Lack Stim1 Protein Expression In Vsmcsmentioning
confidence: 98%
“…Importantly, others have confirmed the regional distribution of SERCA and RyRs not only in pulmonary arterial smooth muscles [ 137 ], but in airway smooth muscles [ 138 ], which may provide for the high degree of variability in kinetics of spontaneous SR calcium release in myocytes from the ileum [ 189 ] and hepatic portal vein [ 126 ]. It is also notable that previous studies have identified RyR1, RyR2 and RyR3 expression in cerebral arterial myocytes [ 139 ], which must at some stage inform current models on calcium signalling in these cells too, which for some reason rely solely on a consideration of RyR2 clusters, whether one considers PM-SR nanojunctions [ 230 , 231 ] or more recent “comparative” assessment of the role of lysosome-SR nanojunctions in this cell type [ 129 ].…”
Section: Reviewing the Situation: Got To Pick A Pocket Or Two Boymentioning
confidence: 99%